2004
DOI: 10.1038/ni1117
|View full text |Cite
|
Sign up to set email alerts
|

GA binding protein regulates interleukin 7 receptor α-chain gene expression in T cells

Abstract: The interleukin 7 receptor alpha-chain (IL-7Ralpha) is essential for T cell development in both humans and mice and for B cell development in mice. Whereas the transcription factor PU.1 regulates IL-7Ralpha expression in mouse pro-B cells via a GGAA motif, we demonstrate here that GA binding protein (GABP) bound to this site and was essential in the regulation of IL-7Ralpha expression in T cells, where PU.1 is not expressed. Moreover, IL-7Ralpha expression was diminished substantially in thymocytes but was nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
172
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(182 citation statements)
references
References 46 publications
9
172
1
Order By: Relevance
“…Yet, the mechanism in CD4 ϩ T cells remains to be deciphered (9). Furthermore, the transcriptional factor GABP␣ has been shown to regulate IL-7R␣ expression in mouse T cells (19). In line with a previous study by Kim et al (24), we found no clear association between expression of IL-7R␣ and GFI-1 or GABP␣ in human lymphocytes, except a subtle increased in GFI-1 expression in naive CD8 ϩ T cells culture with IL-7 (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…Yet, the mechanism in CD4 ϩ T cells remains to be deciphered (9). Furthermore, the transcriptional factor GABP␣ has been shown to regulate IL-7R␣ expression in mouse T cells (19). In line with a previous study by Kim et al (24), we found no clear association between expression of IL-7R␣ and GFI-1 or GABP␣ in human lymphocytes, except a subtle increased in GFI-1 expression in naive CD8 ϩ T cells culture with IL-7 (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…2C, bottom two bars). This result confirms previous findings that the Ets site is essential for activity of the Il7r promoter in T cells (23,30). In summary, these results show that the Ets binding site is required for activity of the Il7r promoter in both B and T cells.…”
Section: An Intact Ets Site Is Essential For Activity Of the Il7r Prosupporting
confidence: 93%
“…EYFP-positive cells were isolated by cell sorting 60 h after transfection, and gene expression in these cells were assessed by real-time PCR as previously described (23). For inducible RNA interference experiments, an oligonucleotide containing a previously described small interfering RNA (5Ј-AGAAGACAGA-AGTTCACCG-3Ј) (23) directed against the coding region of GABP␣ was adapted as a microRNA by ligation into the tetracycline-regulated retroviral vector SIN-TREmi30-PIG (TMP) (Open Biosystems, Huntsville, AL) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Levels of mRNA for the GA-binding protein and Stat5a, which are known to be involved in IL-7R expression and signaling (37,38), were higher in the splenic CD8 ϩ D b NP 366 ϩ set. A determining factor of CTL memory differentiation is the expression of IL-7R during the acute phase of infection (39).…”
Section: Discussionmentioning
confidence: 95%